FRI0111 Change Over Time in the Pattern of Clinical Response to First-Line Biologic Drugs: Observational Data from a Local Registry. (9th June 2015) - Favalli, E.G.; Biggioggero, M.; Becciolini, A.; Marchesoni, A.; Meroni, P.L.
Abstract : Background: The use of biologic drugs (bDMARDs) for the treatment of rheumatoid arthritis (RA) is well established and has progressively changed over time as an effect of the increasing number of available agents and the newly proposed international recommendations. Objectives: To evaluate the change over 15 years of the proportion of bDMARD treated patients achieving a 1-year remission or Low Disease Activity (LDA) in a real-life setting. Methods: RA patients treated with their first bDMARD between January 2000 and December 2014 were selected from a local registry. The analysis was limited to patients with at least 1-year follow-up. The overall proportion of patients achieving a 1-year Disease Activity Score 28 (DAS28) remission (<2.6) or LDA (≥2.6 and <3.2) was evaluated. Sub-analyses after stratification of study population according to period of enrollment (2000-2004, 2005-2009, and 2010-2014) and disease duration (under or over 2 years) were performed by using Fisher's and chi-squared test. Results: The analysis included 676 patients (82.3% female, mean age [± SD] 54.2 [±12.1] years, mean disease duration 9.2 [±8.1]), treated with anti-TNF agents (n=637), abatacept (n=11), tocilizumab (n=22), or rituximab (n=6). In the whole study population 20.8 and 9.4% of patients achieved 1-year remission or LDA, respectively. The rate of 1-year remission or LDA was significantly higher (p<0.0001) for patients enrolled in the period 2010-2014 (31 and 8%, respectively) compared with both 1999-2004 (10 and 9.6%, respectively) and 2005-2009 (24 and 10%, respectively). The relative risk of achieving 1-year remission or LDA was significantly higher in early (<2 years; n=76) compared with late (>2 years; n=601) RA patients (RR 1.629, 95% confidence interval 1.237-2.143; p=0.002). Conclusions: In a real-life setting, about 30% of patients treated with a first-line bDMARD achieved remission or LDA after 1 year of therapy. Patients early receiving bDMARD treatment and beginning the first bDMARD after 2010 showed a significantly higher probability to achieve the therapeutic target. Disclosure of Interest: None declared